Urea Electrooxidation: Current Development and Understanding of Ni‐Based Catalysts - Hu, Xinrang; Zhu, Jiaye; Li, Jiangfeng; Wu, Qingsheng (ChemElectroChem, 2020)
Nowadays, urea‐rich wastewater has become a big threat to human health. Electrocatalytic techniques can convert urea from urea‐rich wastewater to hydrogen for ecological protection and clean energy generation. But, the urea oxidation reaction suffers sluggish kinetics, which requires effective catalysts to promote the oxidation process. Recently, Ni‐based materials have been widely researched as catalysts in the field of urea electrooxidation, owing to their low cost, low overpotential, high current density and good catalytic stability. However, urea‐based fuel cells cannot be compared with other types of cryogenic fuel cells, owing to the high action temperature, sluggish anode reaction for urea electrooxidation and limited current density. In this Review, the morphological structure and elemental content ratio of nickel‐based catalysts for urea electrooxidation and their application in urea‐based fuel cells are summarized. Based on a literature review, the 3D structure of complex nickel‐based composites with high conductivity and abundant active sites will be part of developing trends in the future nickel‐based catalysts. What's trending? The morphological structure and elemental content ratio of nickel‐based catalysts for urea electrooxidation and their application in urea‐based fuel cells are summarized. The 3D structure of complex nickel‐based composites with high conductivity and abundant active sites are expected to be part of developing trends in the future nickel‐based catalysts.